Fault-tolerant Compensation Control Based on Sliding Mode Technique of Unmanned Marine Vehicles Subject to Unknown Persistent Ocean Disturbances - Hao, Li-Ying; Zhang, He; Yue, Wei; Li, Hui (International journal of control, automation, and systems, 2020)
This paper is concerned with a robust adaptive fault-tolerant compensation control problem based on sliding mode technique for an unmanned marine vehicle (UMV) with thruster faults and unknown persistent ocean disturbances. A general thruster fault model including partial, total and time-varying stuck is built for the first time. Once the thrusters occur unknown and time-varying stuck faults, the mission of the UMV may be canceled. To avoid it, full-rank decomposition of the thruster configuration matrix is made, based on which a linear sliding surface is constructed and adaptive mechanism is incorporated into sliding mode reaching law. Without the prior knowledge of ocean external disturbances, sliding mode stability is analyzed and a sufficient stability condition through H ∞ technique is given. Further the nonlinear unit vector gain of the adaptive sliding mode fault-tolerant compensation controller is designed to ensure the UMV system errors converge to zero independent of fault detection and diagnosis (FDD) mechanism. Finally, the comparison simulation results through a typical floating production ship are shown to testify the feasibility of the presented method.